KONSTRUKSI KOMPOR BRIKET BATUBARA UNTUK EFISIENSI INDUSTRI KECIL DAN MENENGAH - Subiantoro, Irfan; Trilaksono, Ardhian; Syarif, Ahmad Bazi (Otopro, 2025)
Small and Medium Industry is an industry that operates in the field of processing raw materials into products that can increase sales value. In the industrial world, business actors are required to process raw materials in large quantities and can reduce costs to make them cheaper. Coal briquette stoves that exist in society have many shortcomings, therefore researchers will make a coal briquette stove by changing the capacity of the briquette fuel container, designing temperature settings, and setting the ideal stove height. With increasing energy needs and the high price of fossil fuels, coal briquette stoves offer a more affordable alternative for small and medium enterprises (IKM) and are more environmentally friendly. This design explains the process of making a stove, from selecting raw materials to optimal design for industrial use. Apart from that, this article also examines the performance and efficiency of stoves in real applications, as well as their benefits in reducing emissions and increasing the productivity of Small and Medium Industries (IKM). The results show that the use of coal briquette stoves not only reduces operational costs but also supports environmental sustainability so that it is feasible to be widely implemented in the Small and Medium Industry (IKM) sector